STATUS AKREDITASI DAN KUALITAS SEKOLAH DI SEKOLAH DASAR NEGERI - Setiyaningsih, Charisma Dewi (Universitas Negeri Malang, 2017)
Abstract: The aims of this research are to investigate: (1) the status school accreditation,(2) the school performance, (3) the relationship between accreditations standards and schoolperformance. The research uses quantitative approach with correlational descriptive design.Participants of this study consist of 65 school including State Elementary School, in BatuRegion that were selected through area sampling. Data were collected through surveyquestionares and analysed using descriptive analysis and Spearman Rank correlation. Thefindings are as follows: the majority of schools are accredited B, the school obtained higherperformance of management operation, and there is a relations between status accreditationsand school performance.keyword: status accreditation, school performanceAbstrak: Penelitian ini bertujuan untuk mengetahui (1) tingkat akreditasi sekolah, (2) tingkatkulitas sekolah, dan (3) hubungan antara status akreditasi sekolah dengan kualitas sekolah.Penelitian ini menggunaan metode penelitian korelasional. Populasi dalam penelitian adalah65 Sekolah Dasar (SD) Negeri di Kota Batu, dan menggunakan teknik area sampling.Selanjutnya teknik analisis yang digunakan adalah teknik analisis deskriptif dan teknikanalisis korelasi Spearman Rank. Hasil penelitian menunjukkan bahwa, mayoritas SDN diKota Batu terakreditasi B sebanyak 26%, kualitas sekolah berada dalam kategori tinggi, danterdapat hubungan antara status akreditasi sekolah dengan kualitas sekolah.Kata kunci: status akreditasi sekolah, kualitas sekolah